Competition in the global electronics display industry: strategies of major players. (4th August 2014) - Bowonder, B.; Sarnot, S.L.; Rao, M.S.; Miyake, T.
Electronic information displays represent one of the strategic product industries which are likely to shape the information revolution. Currently, large Japanese firms dominate some segments of this market. The information and communications technology industry is one of the fastest growing segments of global industry. This paper analyzes the competitive trends in global information display industry. It is divided into three sections. First, an overview of the global display industry is presented. Then, initiatives in display technology used by the major Japanese, US, Taiwanese and South Korean firms are analyzed. Finally the future direction of display technology and strategies will be presented.